Forecasting and Mapping of Vulnerable Areas Floods and Droughts in Rice Crops Impacts of Climate Change In 2022 in East Java Province - Fatikhul Karim; Yuningsih; Agus Fahmi; Cicilia Nova Ratnasari; Amelia Seftiarini (Future Science, 2022)
The impact of climate change has a major impact on the agricultural sector, especially rice crops. The consequences of climate change include floods and droughts which can reduce production. In 2021, East Java was affected by floods in an area of ??14,158.31 hectares of rice plants and 9,195.39 hectares of drought affected by drought. Information on forecasting and mapping of floods and droughts in rice crops is needed. This study aims to obtain forecasts of affected areas and mapping of flood and drought prone areas in certain space and time units. The study uses historical data on flood and drought events for the last 10 years in East Java and analyzed using time series forecasting models and hazard forecasts and interpreted in maps using QGIS software. The flood forecasting model is obtained Log (Y) = 1.657 + 0.406 Log (X) R2 0.74 with a forecast number of flood events in 2022 covering an area of ??11,837.66 Ha. The drought forecasting model obtained Log (Y) = 0.977 + 0.647 Log (X) R2 0.72 with a forecast number of drought events in 2022 covering an area of ??5815.20 Ha. The forecast mapping for the highly flood-prone areas in East Java is Bojonegoro and Gresik regencies, while the flood-prone categories are Tuban, Lamongan, and Lumajang regencies. For mapping areas, the category of very drought-prone areas is Bojonegoro and Lamongan Districts, while the drought-prone category is Trenggalek Regency. Flood and Drought Forecasting and Mapping can be used as initial information on alertness and as a basis for preparing anticipatory, mitigation and adaptation strategies in order to minimize loss of agricultural production.